2011
DOI: 10.1007/s11033-011-0907-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of 1347 G/A cytochrome P450 4F2 (CYP4F2) gene variant with hypertension and stroke

Abstract: Genetic variants of cytochrome P450 4F2 (CYP4F2) gene have been suggested to be risk factors for hypertension, cardiovascular diseases and stroke. In the present case-control study we investigated the association of 1347 G/A polymorphism (rs2108622) in the 11th exon region of CYP4F2 gene with hypertension, ischemic stroke and stroke subtypes classified according to TOAST (Trial of Org 10172 in Acute Stroke Treatment) classification. Five hundred and seven stroke patients (hypertensives: normotensives = 279:228… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 28 publications
5
35
2
Order By: Relevance
“…Apart from the rs9333025 variant, there were no significant differences in association with IS identified for other variants using a singlelocus analytical approach. These results were consistent with those of some previous studies 29,34,35) and in contrast to some others 20,22,[25][26][27][28][36][37][38] . For instance, Gschwendtner et al have reported that genetic variations in the EPHX2 gene are associated with IS risk, an association that has been described as predominantly mediated by large-vessel disease 36) .…”
Section: Logistic Regression Analysissupporting
confidence: 94%
See 4 more Smart Citations
“…Apart from the rs9333025 variant, there were no significant differences in association with IS identified for other variants using a singlelocus analytical approach. These results were consistent with those of some previous studies 29,34,35) and in contrast to some others 20,22,[25][26][27][28][36][37][38] . For instance, Gschwendtner et al have reported that genetic variations in the EPHX2 gene are associated with IS risk, an association that has been described as predominantly mediated by large-vessel disease 36) .…”
Section: Logistic Regression Analysissupporting
confidence: 94%
“…These findings indicate that interactions of rs17110453, rs751141, and rs9333025 could potentially provide these individuals with lower circulating EET levels and higher 20-HETE levels than those without this particular three-gene-variant interaction, thereby increasing the risk of IS. According to previous studies [20][21][22][25][26][27][28][29] and the results of this study, rs17110453AA, rs751141AA, and rs9333025AA are low-risk genotypes. Thus, the associations between IS and different combinations of genotypes were compared with rs17110453AA, rs751141AA, and rs9333025AA.…”
Section: Logistic Regression Analysissupporting
confidence: 74%
See 3 more Smart Citations